Iron-based Prussian blue positive electrode material with improved stability and preparation method of iron-based Prussian blue positive electrode material

When preparing iron-based Prussian blue cathode material, the coordination effect of perchlorate ions and sodium citrate is used to reduce the crystallization water content, and the problem of poor stability of existing materials is solved, and higher cycling and electrochemical properties are achieved.

CN119873861AActive Publication Date: 2025-04-25HUAZHONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510211505.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-25
Estimated Expiration
2045-02-25

AI Technical Summary

Technical Problem

The existing iron-based Prussian blue cathode material has poor stability and poor circulation performance due to the presence of crystallization water. The side reaction between crystallization water and electrolyte leads to gas production, deteriorating battery performance.

Method used

Iron Prussian blue positive electrode material was obtained by dissolving ferrous salt, perchlorate and sodium citrate in water, mixing, reacting under stirring, then aging, and separation by solid-liquid separation, washing and drying. This method reduces the content of crystallization water and improves the stability of the material through the adsorption of perchlorate ions and the coordination of ferrous ions.

Benefits of technology

It effectively reduces the crystal water content in the iron-based Prussian blue positive electrode material, improves the stability and circulation performance of the material, extends the service life of sodium ion batteries, and reduces the side reaction with the electrolyte, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873861A_ABST
    Figure CN119873861A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of production of sodium ion battery positive electrode materials, and particularly relates to an iron-based Prussian blue positive electrode material with improved stability and a preparation method of the iron-based Prussian blue positive electrode material. Comprising the following steps: dissolving ferrite, perchlorate and sodium citrate in water to obtain a solution A; dissolving sodium ferrocyanide and an antioxidant in water to obtain a solution B; mixing the solution A and the solution B, stirring and reacting to obtain a suspension; and standing and aging the turbid liquid, and then carrying out solid-liquid separation, washing and drying to obtain the iron-based Prussian blue positive electrode material. The iron-based Prussian blue positive electrode material prepared by the invention can be applied to a sodium ion battery, and the long cycle performance of the sodium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of production of positive electrode materials for sodium ion batteries, and in particular relates to an iron-based Prussian blue positive electrode material with improved stability and a preparation method thereof. Background Art

[0002] Sodium-ion batteries are very similar to lithium-ion batteries in terms of working principle, and have the huge advantage of cheap and readily available raw materials. They are very promising candidate batteries for large-scale grid energy storage. In order to realize the industrialization and industrialization of sodium-ion battery technology, it is very necessary to develop a suitable sodium-ion embedded cathode material.

[0003] Among them, Prussian blue analogs (PBAs) have an open three-dimensional framework structure, large interstitial sites and ion transport channels, which facilitate the reversible insertion and extraction of sodium ions and are ideal cathode materials for sodium ion batteries. Based on comprehensive consideration of factors such as material cost, environmental friendliness and electrochemical performance, iron-based Prussian blue (molecular formula Na2Fe[Fe(CN)6]) with dual active sites is considered to be a highly potential commercial cathode material for sodium ion batteries and has been widely studied.

[0004] However, due to the presence of lattice vacancies and crystal water, PBAs often show poor rate performance and rapid capacity decay in practical applications. It is generally believed that crystal water is the main factor causing the structural instability of PBAs. Studies have shown that crystal water is not only easy to react with the electrolyte, but also cause Na + Gas is generated during the insertion and extraction process, and may also react with Na + Hydration (NaH2O) + Unit, hindering Na + The migration of water of crystalline solids causes accumulated stress and lattice distortion, which eventually leads to capacity decay. However, in the existing liquid phase synthesis technology, these crystalline water will inevitably be introduced into the open framework of PBAs. Therefore, it is crucial to explore reasonable methods to regulate the crystalline water content in the framework to obtain highly stable PBAs.

[0005] Prior art CN 118419950 A discloses a method for preparing a high-quality Prussian blue compound (PB) and its analogue (PBA) for a positive electrode of a sodium ion battery. This synthesis method inevitably introduces crystal water into the Prussian blue lattice. During the circulation process, part of the crystal water exists in the form of hydrated sodium ions, which hinders the migration of sodium ions and is accompanied by cumulative distortion of the Prussian blue crystal structure. In addition, part of the crystal water reacts with the electrolyte to produce gas, which deteriorates the battery performance.

[0006] Prior art CN115108566A discloses a method for preparing a long-life iron-based Prussian blue positive electrode material. The invention significantly improves the cycle stability of the iron-based Prussian blue positive electrode material by dispersing the initial iron-based Prussian blue material synthesized by sodium citrate-assisted coprecipitation in a certain amount of deionized water under inert atmosphere protection, and adding a small amount of alcohol dispersant. However, it does not solve the problem of more crystal water in the iron-based Prussian blue positive electrode material prepared by conventional coprecipitation method. The iron-based Prussian blue obtained by this technology still contains more crystal water, which is not only easy to react with the electrolyte, but also causes Na + Gas is generated during the insertion and removal process. Summary of the invention

[0007] In view of the defects of the prior art, the present invention provides an iron-based Prussian blue positive electrode material with improved stability and a preparation method thereof, the purpose of which is to solve the technical problem that the iron-based Prussian blue positive electrode material in the prior art has poor stability due to the presence of crystal water.

[0008] In order to achieve the above-mentioned object of the invention, according to a first aspect of the present invention, a method for preparing an iron-based Prussian blue positive electrode material with improved stability is provided, characterized in that it comprises the following steps:

[0009] (1) dissolving ferrous salt, perchlorate and sodium citrate in water to obtain solution A;

[0010] (2) dissolving sodium ferrocyanide and an antioxidant in water to obtain a solution B;

[0011] (3) mixing the solution A and the solution B to obtain a suspension;

[0012] (4) The suspension is allowed to stand for aging, and then solid-liquid separation is performed, and then the suspension is washed and dried to obtain an iron-based Prussian blue positive electrode material.

[0013] Preferably, the ferrous salt is selected from one or more of ferrous chloride, ferrous sulfate, ferrous perchlorate, ferrous acetate and ferrous nitrate.

[0014] Preferably, the perchlorate is selected from ferrous perchlorate, sodium perchlorate, potassium perchlorate, and calcium perchlorate.

[0015] Preferably, the antioxidant is selected from one or more of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, tert-butylhydroquinone or ascorbic acid.

[0016] Preferably, in step (1), the concentration of ferrous ions in solution A is 0.01 to 10 mol / L; the molar ratio of perchlorate ions in solution A to ferrous ions in solution A is (1 to 20):1; and the molar ratio of sodium citrate to ferrous ions in solution A is (1 to 10):1.

[0017] Preferably, in step (2), the concentration of the sodium ferrocyanide in the solution B is 0.01 to 10 mol / L; the concentration of the antioxidant in the solution B is 0.001 to 0.1 mol / L.

[0018] Preferably, the volume ratio of the solution A to the solution B is (0.5-2):1.

[0019] Preferably, in step (3), the solution A and the solution B are reacted under stirring conditions, the stirring rate is 300 to 1000 r / min, the stirring time is 2 to 4 h, and the reaction temperature is 25 to 40°C.

[0020] Preferably, in step (4), the aging temperature is 25-40°C, and the aging time is 6-30 hours; in step (4), the drying is carried out in a vacuum oven, the drying temperature is 100-120°C, and the drying time is 12-24 hours.

[0021] According to another aspect of the present invention, there is provided an iron-based Prussian blue positive electrode material with improved stability prepared by the preparation method.

[0022] According to another aspect of the present invention, there is provided an application of the iron-based Prussian blue positive electrode material with improved stability, and the iron-based Prussian blue positive electrode material is applied to a sodium ion battery.

[0023] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0024] (1) The present invention adds ferrous salt and perchlorate. First, since the binding energy between ferrous ions and perchlorate ions is lower than the binding energy between ferrous ions and water molecules, ferrous ions in the solution are more inclined to coordinate with perchlorate ions rather than with water molecules, which can effectively reduce the crystal water content of Fe-based Prussian blue during the crystal nucleation and growth process. Secondly, the adsorption energy of perchlorate ions on the surface of Fe-based Prussian blue crystals is also lower than the adsorption energy of water molecules on the surface of Fe-based Prussian blue crystals. The crystal surface is more inclined to adsorb perchlorate ions, thereby greatly preventing water molecules from entering the interior of Fe-based Prussian blue crystals during crystal growth and aging, thereby reducing its crystal water content. In addition, due to the coordination effect between perchlorate ions and ferrous ions, the ferrous ions and [Fe(CN)6] are competitively inhibited.4- The combination of ions can reduce the occurrence of spontaneous nucleation and precipitation and slow down the crystallization rate. Slowing down the crystallization rate can reduce vacancy defects, thereby preventing water molecules from filling the vacancies. Therefore, reducing vacancies can also reduce the content of crystallization water.

[0025] (2) The sodium citrate of the present invention has a strong complexing ability and can form a coordination compound with ferrous ions, competitively inhibiting the reaction between ferrous ions and [Fe(CN)6] 4- The combination of ferrous ions and citrate ions can reduce the occurrence of spontaneous nucleation and precipitation, slow down the crystallization rate by making ferrous ions preferentially complex with citrate ions, and thus reduce the content of crystallization water; the addition of antioxidants can prevent the oxidation of ferrous ions and increase the sodium content in iron-based Prussian blue, thereby hindering water molecules from filling the gaps, thereby improving its stability and electrochemical properties.

[0026] (3) The iron-based Prussian blue positive electrode material prepared by the present invention has a nanoscale structure and has the advantage of low interstitial water. The preparation method is low in cost and high in efficiency. It is used in sodium ion batteries and has excellent long cycle performance and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The X-ray diffraction (XRD) patterns of the iron-based Prussian blue positive electrode materials prepared in the examples and comparative examples.

[0028] Figure 2 The following are scanning electron microscope images (SEM) of the iron-based Prussian blue positive electrode materials prepared in the examples and comparative examples; wherein a is example 1; b is example 2; c is example 3; d is comparative example 1; and e is comparative example 2.

[0029] Figure 3 The figure is a comparison chart of the cycle performance of the iron-based Prussian blue positive electrode material prepared in the embodiment and the comparative example. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] Example 1

[0032] Preparation of an iron-based Prussian blue positive electrode material:

[0033] (1) At 30° C., 5 mmol of ferrous perchlorate and 25 mmol of trisodium citrate were dissolved in 100 ml of deionized water to obtain solution A;

[0034] (2) Dissolve 5 mmol of sodium ferrocyanide and 0.1 g of ascorbic acid in 100 ml of deionized water at 30°C to obtain solution B;

[0035] (3) Under the condition of a stirring rate of 300 r / min, solution A was directly poured into solution B, and the mixture was stirred for reaction for 2 hours, then aged at room temperature of 25° C. for 24 hours, and then solid-liquid separation, washing, and drying were performed to obtain an iron-based Prussian blue positive electrode material.

[0036] Figure 1 XRD diagram of the positive electrode material prepared in this example; Figure 2 Figure a is a SEM photo of the positive electrode material prepared in this example. It can be seen from the figure that the material has a cubic phase structure and is composed of cubic particles of 200nm-1μm. Electrochemical tests were performed on it. Figure 3 It can be seen that at a current density of 5C, it has 112.47 mAh g -1 The discharge specific capacity is 80.11% after 1000 cycles.

[0037] Example 2

[0038] Preparation of an iron-based Prussian blue positive electrode material:

[0039] (1) At 30° C., 5 mmol of ferrous chloride, 10 mmol of sodium perchlorate, and 25 mmol of trisodium citrate were dissolved in 100 ml of deionized water to obtain solution A;

[0040] (2) Dissolve 5 mmol of sodium ferrocyanide and 0.1 g of ascorbic acid in 100 ml of deionized water at 30°C to obtain solution B;

[0041] (3) Under the condition of a stirring rate of 800 r / min, solution A was directly poured into solution B, and the mixture was stirred for reaction for 2 hours, then aged at room temperature of 25° C. for 24 hours, and then solid-liquid separation, washing, and drying were performed to obtain an iron-based Prussian blue positive electrode material.

[0042] Figure 1 XRD of the positive electrode material prepared in this example, Figure 2 Figure b is a SEM photo of the positive electrode material prepared in this example. It can be seen from the figure that the material has a cubic phase structure and is composed of cubic particles of 200nm-700nm. Electrochemical tests were performed on it. Figure 3 It can be seen that at a current density of 5C, it has 114.05 mAh g -1 The discharge specific capacity is 1.38W, and the capacity retention rate after 1000 cycles is 70.25%.

[0043] Example 3

[0044] Preparation of an iron-based Prussian blue positive electrode material:

[0045] (1) At 30° C., 5 mmol of ferrous sulfate, 10 mmol of sodium perchlorate, and 25 mmol of trisodium citrate were dissolved in 100 ml of deionized water to obtain solution A;

[0046] (2) Dissolve 5 mmol of sodium ferrocyanide and 0.1 g of ascorbic acid in 100 ml of deionized water at 30°C to obtain solution B;

[0047] (3) Under the condition of a stirring rate of 1000 r / min, solution A was directly poured into solution B, and the mixture was stirred for reaction for 2 hours, then aged at room temperature of 25° C. for 24 hours, and then solid-liquid separation, washing, and drying were performed to obtain an iron-based Prussian blue positive electrode material.

[0048] Figure 1 XRD of the positive electrode material prepared in this example, Figure 2 Figure c is a SEM photo of the positive electrode material prepared in this example. It can be seen from the figure that the material has a cubic phase structure and is composed of cubic particles of 200nm-700nm. Electrochemical tests were performed on it. Figure 3 It can be seen that at a current density of 5C, it has 112.04 mAh g -1 The discharge specific capacity is 2.12% after 1000 cycles.

[0049] Comparative Example 1

[0050] Preparation of an iron-based Prussian blue positive electrode material:

[0051] (1) At 30°C, 5 mmol of ferrous chloride and 25 mmol of trisodium citrate were dissolved in 100 ml of deionized water to obtain solution A;

[0052] (2) Dissolve 5 mmol of sodium ferrocyanide and 0.1 g of ascorbic acid in 100 ml of deionized water at 30°C to obtain solution B;

[0053] (3) Under the condition of a stirring rate of 800 r / min, solution A was directly poured into solution B, and the mixture was stirred for reaction for 2 hours, then aged at room temperature of 25° C. for 24 hours, and then solid-liquid separation, washing, and drying were performed to obtain an iron-based Prussian blue positive electrode material.

[0054] Figure 1 The XRD diagram of the positive electrode material prepared in this comparative example is: Figure 2 Figure d is a SEM photo of the positive electrode material prepared in this comparative example. It can be seen from the figure that the material has a cubic phase structure and is composed of cubic particles of 200nm-400nm. Electrochemical tests were performed on it. Figure 3It can be seen that at a current density of 5C, it has 115.76 mAh g -1 The discharge specific capacity is 59.04% after 1000 cycles.

[0055] Comparative Example 2

[0056] Preparation of an iron-based Prussian blue positive electrode material:

[0057] (1) Dissolve 5 mmol of ferrous sulfate and 25 mmol of trisodium citrate in 100 ml of deionized water at 30° C. to obtain solution A;

[0058] (2) Dissolve 5 mmol of sodium ferrocyanide and 0.1 g of ascorbic acid in 100 ml of deionized water at 30°C to obtain solution B;

[0059] (3) Under the condition of a stirring rate of 1000 r / min, solution A was directly poured into solution B, and the mixture was stirred for reaction for 2 hours, then aged at room temperature of 25° C. for 24 hours, and then solid-liquid separation, washing, and drying were performed to obtain an iron-based Prussian blue positive electrode material.

[0060] Figure 1 The XRD diagram of the positive electrode material prepared in this comparative example is: Figure 2 Figure e is a SEM photo of the positive electrode material prepared in this comparative example. It can be seen from the figure that the material has a cubic phase structure and is composed of cubic particles of 200nm-400nm. Electrochemical tests were performed on it. Figure 3 It can be seen that at a current density of 5C, it has 112.49 mAh g -1 The discharge specific capacity is 2.5477 W, and the capacity retention rate after 1000 cycles is 66.92%.

[0061] Table 1 Cyclic capacity of iron-based Prussian blue positive electrode materials prepared in Examples and Comparative Examples

[0062]

[0063] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an iron-based Prussian blue positive electrode material with improved stability, characterized in that: The steps include: (1) dissolving ferrous salt, perchlorate and sodium citrate in water to obtain solution A; (2) dissolving sodium ferrocyanide and an antioxidant in water to obtain a solution B; (3) mixing the solution A and the solution B to obtain a suspension; (4) The suspension is allowed to stand for aging, and then solid-liquid separation is performed, and the iron-based Prussian blue positive electrode material is obtained after washing and drying.

2. The method for preparing an iron-based Prussian blue positive electrode material with improved stability according to claim 1, characterized in that: The ferrous salt is selected from one or more of ferrous chloride, ferrous sulfate, ferrous perchlorate, ferrous acetate, and ferrous nitrate; the perchlorate is selected from ferrous perchlorate, sodium perchlorate, potassium perchlorate, and calcium perchlorate.

3. The method for preparing an iron-based Prussian blue positive electrode material with improved stability according to claim 1, characterized in that: The antioxidant is selected from one or more of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, tert-butylhydroquinone or ascorbic acid.

4. The method for preparing an iron-based Prussian blue positive electrode material with improved stability according to claim 1, characterized in that: In step (1), the concentration of ferrous ions in solution A is 0.01-10 mol / L; the molar ratio of perchlorate ions in solution A to ferrous ions in solution A is (1-20):1; and the molar ratio of sodium citrate to ferrous ions in solution A is (1-10):

1.

5. The method for preparing an iron-based Prussian blue positive electrode material with improved stability according to claim 4, characterized in that: In step (2), the concentration of the sodium ferrocyanide in the solution B is 0.01 to 10 mol / L; the concentration of the antioxidant in the solution B is 0.001 to 0.1 mol / L.

6. The method for preparing an iron-based Prussian blue positive electrode material with improved stability according to claim 5, characterized in that: The volume ratio of the solution A to the solution B is (0.5-2):

1.

7. The method for preparing an iron-based Prussian blue positive electrode material with improved stability according to claim 1, characterized in that: In step (3), the solution A and the solution B are reacted under stirring conditions, the stirring rate is 300 to 1000 r / min, the stirring time is 2 to 4 hours, and the reaction temperature is 25 to 40°C.

8. The method for preparing an iron-based Prussian blue positive electrode material with improved stability according to claim 1, characterized in that: In step (4), the aging temperature is 25-40° C., and the aging time is 6-30 hours; in step (4), the drying is carried out in a vacuum oven, the drying temperature is 100-120° C., and the drying time is 12-24 hours. 9 . An iron-based Prussian blue positive electrode material with improved stability prepared by the preparation method according to claim 1 .

10. The use of the iron-based Prussian blue positive electrode material with improved stability according to claim 9, characterized in that: The iron-based Prussian blue positive electrode material is applied to sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of long-life iron-based Prussian blue positive electrode material

    CN115108566A